Diagnostic tests in Raynaud's phenomena in workers exposed to vibration: a comparative study. Issue 6 (June 1988) - Olsen, N
Abstract : Four objective tests to evaluate Raynaud's phenomena (RP) in workers exposed to handarm vibrations were applied on 23 exposed men with RP (vibration induced white finger 18, primary Raynaud's phenomenon 5), 56 exposed men without RP, and 15 male controls. Finger systolic blood pressure was measured by a cuff and strain gauge technique after combined body cooling and finger cooling during five minute ischaemia to 30 degrees, 15 degrees, and 6 degrees C. An attack of RP was detected as a zero pressure, FSP(0) test, whereas a pressure, reduced to a value below the normal 95% confidence limit at 6 degrees C, was regarded as an abnormal response, FSP(A) test. A hand cooling, preceded by 30 minute body precooling, was performed in water at 10 degrees C during five minute ischaemia. The finger colours after hand cooling were evaluated by a directly visual inspection, FCV test, and by a blind assessment of slides of the photographed hand, FCS test. A medical interview was used as a method of reference. The sensitivity did not differ significantly between FSP(0) (74%), FCS (61%), and FCV (57%) (p greater than 0.10). FSP(A) had a significantly higher sensitivity (96%) and lower specificity (64%) than those of FCV and FCS (p less than 0.0005) and of FSP(0) (p less than 0.05). Six of the seven men with a false positive FSP(0) had a positive FCV or FCS, and the seventh had a history of previously active RP. The six false negative FSP(0) test results did not correspond significantly to milder cases of RP (p greater than 0.20). The results indicate that a finger colour test may be as valuable as a FSP(0) test for diagnostic purposes. FSP(A) only indicates if a cold response is exaggerated and does not diagnose RP. The pressure measurements may further be of guidance in evaluating preventive measures and effects of treatments for RP.